The Chupacabra Ate the Candelabra - Nobleman, Marc Tyler; Aranda, Ana (New York, NY : Nancy Paulsen Books, 2017)
Three anxious goats scramble to avoid being eaten by the legendary chupacabra, whose favorite food is not what they expect.
Keywords: Chupacabras -- Juvenile fiction; Goats -- Juvenile fiction; Food habits -- Juvenile fiction; Chupacabras -- Fiction; Goats -- Fiction; Food habits -- Fictiom